2013
DOI: 10.1590/s1516-14392013005000119
|View full text |Cite
|
Sign up to set email alerts
|

From numerical calculations to materials testing homologation: a biaxial fatigue reliability prediction methodology for structural components

Abstract: This article investigates a fatigue approach conducted from the design phase to testing approval. It considerers modern analytical and experimental tools for structural durability assessment over each development phase for two reference components aiming an early approval methodology validation for a new design. A Finite element analysis procedure was used to set critical spots for measurements minimizing the data acquisition efforts. Based on measured data, strain life calculation was done for two reference c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…It would also be worthwhile to crosscheck the present results with analytical or numerical models, to investigate the influence of tire stiffness and mass upon the developed structural vibration modes. Spinelli et al [19] recently discussed the interplay between finite element modeling and physical tests for vehicle project validation. Also, a classification of the load events as the one recently introduced by Yunoh et al [20] could be attempted.…”
Section: Resultsmentioning
confidence: 99%
“…It would also be worthwhile to crosscheck the present results with analytical or numerical models, to investigate the influence of tire stiffness and mass upon the developed structural vibration modes. Spinelli et al [19] recently discussed the interplay between finite element modeling and physical tests for vehicle project validation. Also, a classification of the load events as the one recently introduced by Yunoh et al [20] could be attempted.…”
Section: Resultsmentioning
confidence: 99%
“…The Swing Motion Bogie with sufficient fatigue strength can be used up to the endurance life of a freight car, and the maximum stress in bolster area is Von-Mises stress on side frame [14]. Additionally, the biaxial fatigue reliability prediction methodology and some fatigue safety life assessment research related to large complex structural parts, like the aircraft engine support structure, can also be used as references in the structural safety evaluation of the bolster in the near future [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Research on multi-axial loading equipment has been recently reported, including biaxial tension and compression tests (Zhang and Zhang, 2013;Smoger et al, 2012;O'Connell et al, 2012, biaxial fatigue tests (Spinelli et al, 2013), triaxial tension and compression test (Feng et al, 2010;Lee et al, 2013;Soroush and Jannatiaghdam, 2012;Cil and Alshibli, 2014). Most of the mentioned biaxial and triaxial material tests are based on the composing of orthogonal uniaxial load cell actuated by hydraulic or electric motors.…”
Section: Introductionmentioning
confidence: 99%